(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
Wayne Blair’s 2012, dramatic comedy The Sapphires is an Australian film that discusses a number of important issues for Indigenous people, including the concept of belonging. Blair explores how belonging can exist both within community groups and internally through self-identity. The bones of the film are based on the true story of Laurel Robinson and Lois Peeler, two Indigenous women who toured Vietnam as the original ‘Sapphires’ with a New Zealand Maori band (Herche 2013). Laurel Robinson’s son, Tony Briggs wrote the screenplay and the 2004 musical (of the same name) thus being able to add a sense of authenticity. The film opens up a side of Australian history that has previously been underrepresented but has a universal appeal through its representation of belonging.